A preliminary comparative outlook on Turkish and Malay adult learners’ cultural orientations in education - Ahmad, Badli Esham; Ozturk, Mustafa; Khalid, Fairuz; Abdul Majid, Faizah; Abdullah, Mohd Amli (GADING Journal for the Social Sciences, 2024)
The current trend in education is shifting towards the autonomous learner, whereby learning has shifted from the traditional face-to-face classroom into more open and distance online learning. The advancement of Web 2.0 has allowed for a different approach to learning. Online classroom interaction is different from that of normal face-to-face (F2F) interaction in the classroom. The physical presence in the class may inhibit certain behaviours among the learners. The objective of the study is to determine if Malay and Turkish adult learners are influenced by their cultural values in their education. The study employed the quantitative method, where a survey was used to collect the required data. It is a preliminary study aimed at determining the cultural orientations of the respondents and deducing the implications of suitable learning approaches based on the findings. The study found that Malay adult learners are not influenced by their cultural values, whereas Turkish learners are influenced by their cultural values. The study shows that cultural values play a role in these learners (Malay and Turkish), but the degree of the influence varies.